The Eel Story: Myth, Memory, and the Politics of Religious Persecution in Seventeenth-Century Aceh - Thalal, Muhammad; Thalal, Raja Mumtaz (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2026)
This article examines the eel story. This narrative is a multi-generational family myth from the Krueng Kalee clan in Aceh, Indonesia. The study investigates how the narrative preserves memories of religious persecution through the use of mythological elements. The research utilizes a qualitative approach. The data consists of in-depth interviews with four tradition bearers selected through purposive sampling. The analysis involves thematic coding and narrative evaluation. Researchers conducted member checking and cross confirmation to ensure data validity. The findings reveal that the story functions as a site of memory for the descendants. The narrative establishes a significant food taboo as a response to ancestral trauma. This article suggests that the story may operate as a hidden transcript. The dietary practice suggests potential historical connections to minority Islamic traditions during the seventeenth-century Aceh Sultanate. This study demonstrates how specific family myths protect marginalized identities in restrictive religious environments.